Modeling the Economic Impact of Substandard and Falsified Antimalarials in the Democratic Republic of the Congo - Ozawa, Sachiko (Am J Trop Med Hyg, 2019)
Substandard and falsified medicines pose significant risks to global health, including increased deaths, prolonged treatments, and growing drug resistance. Antimalarials are one of the most common medications to be of poor quality in low- and middle-income countries. We assessed the health and economic impact of substandard and falsified antimalarials for children less than 5 years of age in the Democratic Republic of the Congo, which has one of the world’s highest malaria mortality rates. We developed an agent-based model to simulate patient care-seeking behavior and medicine supply chain processes to examine the impact of antimalarial quality in Kinshasa province and Katanga region. We simulated the impact of potential interventions to improve medicinal quality, reduce stockouts, or educate caregivers. We estimated that substandard and falsified antimalarials are responsible for $20.9 million (35% of $59.6 million; 95% CI: $20.7–$21.2 million) in malaria costs in Kinshasa province and $130 million (43% of $301 million; $129–$131 million) in malaria costs in the Katanga region annually. If drug resistance to artemisinin were to develop, total annual costs of malaria could increase by $17.9 million (30%; $17.7–$18.0 million) and $73 million (24%; $72.2–$72.8 million) in Kinshasa and Katanga, respectively. Replacing substandard and falsified antimalarials with good quality medicines had a larger impact than interventions that prevented stockouts or educated caregivers. The results highlight the importance of improving access to good quality antimalarials to reduce the burden of malaria and mitigate the development of antimalarial resistance.